Roads not taken : an intellectual biography of William C. Bullitt - Ėtkind, Aleksandr, 1955- (Series in Russian and East European studies., 2017)
William Christian Bullitt (1891-1967) was the most cosmopolitan U.S. diplomat of his time. Voted most brilliant in his class at Yale, he wrote novels, plays, essays, and coauthored a controversial biography of President Wilson with Sigmund Freud. A political visionary, his views were often contentious, although he was often proven right by the unfolding of events. Bullitt served the United States through two World Wars and foresaw the collapse of old regimes while becoming a sympathetic expert on both European and Russian socialism. He was a member of the American delegation to the Paris Peace Conference (1918), the first U.S. Ambassador to the Soviet Union (1933-1936), and Roosevelt's Ambassador to France (1936-1940). A friend of the Russian people and an early proponent of friendly relations with the new Soviet government under Lenin, his later experience as ambassador to Moscow led him to be among the first to warn of Stalin's aggressive intentions toward the West. Bullitt worked tirelessly to preserve European democracy until policy disagreements with his friend Franklin Roosevelt eventually sidelined him politically. While his famous disciples, George Kennan and Charles Bohlen, led American diplomacy toward the USSR in the emerging Cold War, Bullitt became an early advocate of European unity. This multi-faceted biography sheds new light on the fascinating, deeply intellectual life of an important political figure who counted Lenin, Roosevelt, Chiang-Kai-Shek, Charles de Gaulle, and Sigmund Freud among his personal relationships in a life profoundly connected to the history of the twentieth century.